Systems Thinking in Practice: Participatory Modeling as a Foundation for Integrated Approaches to Health - Duboz, Raphaël; Echaubard, Pierre; Promburom, Panomsak; Kilvington, Margaret; Ross, Helen; Allen, Will; Ward, John; Deffuant, Guillaume; de Garine-Wichatitsky, Michel; Binot, Aurélie (Frontiers in Veterinary Science, 2018)
One Health (OH), EcoHealth (EH) and Planetary Health (PH) share an interest in transdisciplinary efforts that bring together scientists, citizens, government and private sectors to implement contextualized actions that promote adaptive health management across human, animal and ecosystem interfaces. A key operational element underlying these Integrated Approaches to Health (IAH) is use of Systems Thinking as a set of tools for integration. In this paper we discuss the origins and epistemology of systems thinking and argue that participatory modelling, informed by both systems theory and expertise in facilitating engagement and social learning, can help ground IAH theoretically and support its development. Participatory modelling is iterative and adaptive, which is necessary to deal with complexity in practice. Participatory modelling (PM) methods actively involve affected interests and stakeholders to ground the field of inquiry in a specific social-ecological context. Furthermore, PM processes act to reconcile the diverse understandings of the empirical world that stem from divergent discipline and community viewpoints. In this perspective article, we argue that PM can support systems thinking in practice and is essential for IAH implementation. Accordingly we invite PH, OH and EH practitioners to systematically incorporate specialists in systems science and social engagement and facilitation. This will enable the appropriate contextualization of research practice and interventions, and ensure a balanced representation of the roles and relationships of medical, biological, mathematical, and social disciplines. For completeness, funding schemes supporting IAH need to follow the same iterative, adaptive and participative processes to accompany IAH projects throughout their implementation.